Analisis Keputusan Nasabah Menggunakan Produk Pembiayaan Bank Muamalat Makassar - Kapriani Kapriani (JURNAL MANAJEMEN MOTIVASI, 2013)
The purpose of this study was to determine the effect, cultural, social, personal, psychological and financial products to the customer's decision to use financing at Bank Muamalat in Makassar. Primary and secondary data collection through interviews and questionnaires. Total sample of 100 customers. The results showed that based on multiple linear regression analysis showed that cultural variables (X1), social (X2), personal (X3) and experience (X5) has a positive influence on customer decisions. While the psychological variables (X4) have a negative influence on the decision to use a product financing. Based on the coefficient of determination (R2) financing decisions using the product described by the cultural, social, personal, psychological, and experience of 96.7%. Based on t test results indicate that that the cultural variables (X1), social (X2), psychological (X4) and experience (X5) significantly influence the customer's decision to use a product financing. While the private variable (X3) does not affect the customer's decision to use a product financing. F test indicates that the variable cultural, social, personal, psychological and simultaneously experience a significant influence on  customer decision variables using financing products.Keyword: kebudayaan, sosial, pribadi, psikologis, pengalaman dan keputusan nasabah.